Story writer's ideas journal - Stowell, Louie (Usborne Publishing UK, 2017)
This write-in activity book combines story prompts, writing tips and inspiring quotes from well-known authors, with tips on developing a plot, inventing characters, writing dialogue and setting the scene. There are blank pages to write your own stories and jot down ideas, plus an elastic closure to keep it all together.